Mobile robot path optimization algorithm using vector calculus and mapping of 2 dimensional space - Zahari, Ammar; Ismail , Amelia Ritahani; Desia, Recky (Universiti Teknologi Malaysia, 2015)
This research explores path integration in mobile robot navigation and path optimization technique using vector calculus. A simulated robot in a simulated environment is used to test the algorithm that is to be developed. The simulated robot is equipped with a sonar sensor and several infrared sensors on its chassis. Mobile robot navigation in an unknown environment is very crucial as It not only has to be concerned about reaching its destination but also to avoid obstacles that may be in the way. This algorithm can effectively allow a mobile robot to navigate an unknown environment without collision into obstacles.